Integration of A Web Mdvr Howen Vehicle Surveillance System (Vss) and An Artificial Intelligence Based in Car Camera (Icc) For Fleet Safety PT. Putra Perkasa Abadi Jobsite Adaro Indonesia - Gianina, Lovina; Khadafi, Muammer; Farzan, Arizal; Abidin, Zainal (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The main technology widely applied is the Vehicle Surveillance System (VSS) Web MDVR Howen, a digital surveillance platform that utilizes Mobile Digital Video Recorder, multi angle cameras, GPS, and AI alarms to monitor vehicle activity in real time. The combination of visual data, AI alarms, and behavioral analytics, this system supports the process of recording, validating, and analyzing events. This AI based integration is in line with the needs of modern industry to improve fleet safety, operational efficiency, and compliance with evidence based safety standards. The research aims to analyze the integration of the VSS Web MDVR Howen system and Artificial Intelligence based In Car Camera (ICC) for fleet safety. This research uses a qualitative descriptive method. VSS Web MDVR Howen and AI based In Car Camera (ICC) are two complementary fleet surveillance technologies to form a comprehensive driving safety system. The integration of the VSS Web MDVR Howen system and Artificial Intelligence based In Car Camera (ICC) has been proven to be able to improve the safety of the PT Putra Perkasa Abadi Jobsite Adaro Indonesia fleet through real time monitoring of vehicle conditions and driver behavior. Data analysis from October–November 2025 showed that this technology effectively detected critical deviations such as fatigue and drowsiness, which are key risks, while maintaining compliance with other aspects such as phone bans and camera closures. AI based monitoring enables rapid intervention, automated alerts, and the provision of accurate data for safety evaluation, helping companies strengthen a safe work culture, improve compliance with SOPs, and significantly reduce the potential for accidents.